Sejarah dan pemikiran akuntansi syariah - Maulina, Isra (Jurnal Investasi Islam, 2022)
This paper discusses the history of the birth of sharia accounting which is inseparable from thedevelopment of Islam, the obligation to record non -cash transactions as mentioned in the QS. AlBaqarah: 282 encouraged Muslims to care about recording and gave rise to the tradition ofrecording among the people, and this was one of the factors that encouraged cooperation at thattime. History proves that accounting science has long been practiced in the Islamic world,such as the term journal, which was used during the time of the Islamic caliphate with theterm "jaridah" for financial bookkeeping. Likewise with the double entry written by LucaPacioli. That way we know that Islam first recognized the accounting system because theQur'an was revealed in 610 AD, which is 800 years earlier than Luca Pacioli whopublished his book in 1494. Sharia accounting is accounting which processes financialtransactions using contracts in accordance with the provisions of the Qur'an and Hadithand ijmak. Thus, accounting has been known as a means of accountability to companyowners, so sharia accounting is more than that, namely accountability to company ownersand God.